2001
DOI: 10.1002/rnc.595
|View full text |Cite
|
Sign up to set email alerts
|

Forward decomposition algorithms for optimal control of a class of hybrid systems

Abstract: SUMMARYThis paper considers optimal control problems for a class of hybrid systems motivated by the structure of manufacturing environments that integrate process and operations control. We derive new necessary and su$cient conditions that allow us to determine the structure of the optimal sample path and hence decompose a large non-convex, non-di!erentiable problem into a set of smaller convex, constrained optimization problems. Using these conditions, we develop two e$cient, low-complexity, scalable algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 12 publications
0
68
0
Order By: Relevance
“…Proof: (By contradiction) Let us assume that jobs and are in the same block of the th machine on the optimal sample path, and . From (10), there are two possible cases: Case 1: : From (31), and from (35), . Case 2:…”
Section: B Controllable Machinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Proof: (By contradiction) Let us assume that jobs and are in the same block of the th machine on the optimal sample path, and . From (10), there are two possible cases: Case 1: : From (31), and from (35), . Case 2:…”
Section: B Controllable Machinesmentioning
confidence: 99%
“…In [8], the task of solving these problems was simplified by exploiting structural properties of the optimal sample path, and it was shown that, despite the fact that the objective function was non-convex and non-differentiable, the optimal sample path was unique. Further exploiting the structural properties of the optimal sample path, "backward-in-time" and "forward-in-time" algorithms based on the decomposition of the original non-convex and non-differentiable optimization problem into sets of smaller convex optimization problems with linear constraints were presented in [9] and [10], respectively. The "forward-in-time" algorithm presented in [10] was then improved by Zhang and Cassandras in [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In [6], [7], [8], and [9], the hybrid system framework is adopted to analyze a single-stage manufacturing process assuming a deterministic setting, i.e., a known job arrival schedule and controllable service times for all jobs. An efficient algorithm to determine the optimal service times for a class of single-stage systems is presented in [8].…”
Section: Introductionmentioning
confidence: 99%
“…An efficient algorithm to determine the optimal service times for a class of single-stage systems is presented in [8]. In [10], however, a stochastic model of a single-stage manufacturing system is studied, where the job arrivals are represented through a Poisson process with the control variable being the exponential service's process rate.…”
Section: Introductionmentioning
confidence: 99%